Isotomidae (Collembola) of Buryat Republic. II. A revision of the genus Folsomia - Potapov, Mikhail; Gulgenova, Ayuna (Zootaxa, 2013)
Nine new species of the genus Folsomia are described from Buryatia (Russia, East Siberia): F. biparis sp. nov., F. fumosa sp. nov., F. heterothorax sp. nov., F. maximovi sp. nov., F. pseudovtorovi sp. nov., F. sensivillosa sp. nov., F. uniparis sp. nov., F. uniramia sp. nov., and F. vitimica sp. nov. A complete list and a key to species recorded in the Buryatia are given, and their morphology, distribution, and ecology are annotated. The taxonomical groups of species are discussed.